Integration of Market-Based Contextual Learning in Craft Tasks: a Study of Consumer and Competitor Behavior by Students - Santorini, Nur Barliani; Pradiani, Theresia (LP. Ma'arif Janggan Magetan, 2024)
In the digital era, digital marketing is crucial for expanding business reach and engaging consumers. This study examines PT Sadulur Sinareng Raharja, a digital marketing firm specializing in customized campaigns based on market trends, consumer behavior, and competitor analysis, which is highly relevant to educational institutions with digital marketing programs. Despite its innovative strategies, the company faces challenges such as changing consumer preferences, increasing competition, and declining campaign effectiveness. This study offers practical business insights while also serving as an educational tool, demonstrating the use of data-driven marketing strategies in real-world business contexts. The research, based on quantitative methods and strategic marketing theory, analyzes data from 30 respondents using multiple regression analysis to evaluate the impact of market trends, consumer behavior, and competitor positioning on campaign performance (ROI, conversion rate, and engagement rate). The findings, validated by classical assumption tests, show that all factors significantly affect campaign effectiveness, with an R² value of 77.9%. The results emphasize the importance of a market-driven approach, adaptability to changing trends, and the use of data analytics to create targeted campaigns. This case study is valuable for students and professionals in business and marketing education.